2002
DOI: 10.1042/bj20020107
|View full text |Cite
|
Sign up to set email alerts
|

Ppm1, a novel polyprenol monophosphomannose synthase from Mycobacterium tuberculosis

Abstract: Dolichol monophosphomannose (DPM) is an ever-present donor of mannose (Man) in various eukaryotic glycosylation processes. Intriguingly, the related polyprenol monophosphomannose (PPM) is involved in the biosynthesis of lipomannan and lipoarabinomanan, key bacterial factors termed modulins that are found in mycobacteria. Based on similarities to known DPM synthases, we have identified and characterized the PPM synthase of Mycobacterium tuberculosis, now termed Mt-Ppm1. In the present study, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 33 publications
9
129
1
Order By: Relevance
“…In fact, there are two Lnt homologues in S. coelicolor, SCO1014 and SCO1336. SCO1014 also shows homology to a domain associated with mycobacterial polyprenol monophosphomannose (PPM) synthases [42]. Notably M. tuberculosis Ppm is a two-domain protein (Rv2051c) in which the Nterminus is similar to Lnt and the C-terminus has PPM synthase activity [42].…”
Section: N-acylation In Gram-positive Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, there are two Lnt homologues in S. coelicolor, SCO1014 and SCO1336. SCO1014 also shows homology to a domain associated with mycobacterial polyprenol monophosphomannose (PPM) synthases [42]. Notably M. tuberculosis Ppm is a two-domain protein (Rv2051c) in which the Nterminus is similar to Lnt and the C-terminus has PPM synthase activity [42].…”
Section: N-acylation In Gram-positive Bacteriamentioning
confidence: 99%
“…SCO1014 also shows homology to a domain associated with mycobacterial polyprenol monophosphomannose (PPM) synthases [42]. Notably M. tuberculosis Ppm is a two-domain protein (Rv2051c) in which the Nterminus is similar to Lnt and the C-terminus has PPM synthase activity [42]. PPM is an alkali-stable sugar donor used in the formation of the cell envelope glycolipids lipomannan (LM) and lipoarabinomannan (LAM) in M. tuberculosis [42].…”
Section: N-acylation In Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences corresponding to the C-terminal domain of the Rv2051c gene product (Mt-ppm/D2) required for cloning into pUC8 were obtained by PCR using Vent polymerase (New England Biolabs, Beverly, MA, U.S.A.) as described previously [22]. Liquid cultures of Escherichia coli (pUC8-Mt-ppm1/D2) were grown in LB broth at 37 • C with 100 µg/ml ampicillin to an A 600 0.4 and induced for 4 h with 1 mM isopropyl β-D-thiogalactoside [22].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Besra et al [17] demonstrated that Ac 1 PIM 2 (according to the nomenclature of Kordulakova et al [21]) is specifically extended by an addition of Manp residues from the alkali-stable sugar donor C 50 /C 40 /C 35 -PPM (where PPM stands for polyprenol monophosphomannose) to form higher PIMs and further to a 'linear' α(1 → 6)-LM via a PPM-dependent α(1 → 6)mannosyltransferase. The generation of PPM in M. tuberculosis H37Rv results from the transfer of Manp from GDP-Manp to polyprenyl phosphates catalysed by the C-terminal domain(s) of a PPM synthase (Mt-Ppm1), now termed as Mt-Ppm1/D2 [22]. However, the identity of the mycobacterial PPM-dependent α(1 → 6)mannosyltransferase is unknown.…”
Section: Introductionmentioning
confidence: 99%